Recurrent Escherichia coli Urinary Tract Infection Triggered by Gardnerella vaginalis Bladder Exposure in Mice - O’Brien, Valerie P. (J Vis Exp, 2020)
Recurrent urinary tract infections (rUTI) caused by uropathogenic Escherichia coli (UPEC) are common and costly. Previous articles describing models of UTI in male and female mice have illustrated the procedures for bacterial inoculation and enumeration in urine and tissues. During an initial bladder infection in C57BL/6 mice, UPEC establish latent reservoirs inside bladder epithelial cells that persist following clearance of UPEC bacteriuria. This model builds on these studies to examine rUTI caused by the emergence of UPEC from within latent bladder reservoirs. The urogenital bacterium Gardnerella vaginalis is used as the trigger of rUTI in this model because it is frequently present in the urogenital tracts of women, especially in the context of vaginal dysbiosis that has been associated with UTI. In addition, a method for in situ bladder fixation followed by scanning electron microscopy (SEM) analysis of bladder tissue is also described, with potential application to other studies involving the bladder.